Risk assessment and risk management of contaminants in the feed to food chain. (September 2019) - Radulovic, S; Sefer, D; Markovic, R; Lukic, M; Nikolic, A; Milicevic, D
Abstract: In feed production processes, factories usually produce different mixtures within the same production line. Consequently, remainders of the first-produced feed can stay in the system and be mixed with the following feed charge. This type of transfer (carry-over) is unavoidable in the production systems currently used, and thus, non-medicated feed can be contaminated with veterinary drugs present in a previously manufactured charge of medicated feed. The carry-over of veterinary medicinal products is associated with the risk of residues remaining in the tissues of treated animals at the time of slaughter and poses a health hazard to consumers. Producing safe feed and food products is, first and foremost, a question of good management practices at each stage of the feed and food chain, from primary production to final processing. Primary responsibility for feed safety rests with the feed business operator, who must ensure that all stages of production, processing and distribution under their control are carried out in accordance with relevant legislation, good manufacturing practice and principles contained in the HACCP system. Concrete steps for feed manufacturers to prevent drug carry-over are using one or more approved cleanout procedures of manufacturing equipment, such as cleaning, flushing or sequencing.